Current practice of induction of labour and maternal outcome in ≥37 week of gestation: an observational study - Sheth, Jil Manishkumar; Shrivastava, Anjani; Trivedi, Kedar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: As we know induction is done when benefit to mother and fetus overweigh benefits of continuing the pregnancy. According to NICE guidelines, induction of labor leads to 15% of instrumental deliveries and 22% of total LSCS. In new civil hospital, Surat (according to 2017) failure of induction of labor was 2nd most common indication of LSCS. The objective of this study were to analyse labor induction with respect to indication for induction of labor and its maternal outcome so that we optimize our protocol of labor and reduce our LSCS rates for the same, can reduce feto-maternal morbidities also. Methods: This was prospective observational descriptive study carried out over duration of 6 month. 200 consecutive cases of consenting women requiring induction of labour and fulfilling inclusion criteria were selected. Induction was done with prostaglandin analogous. Data were collected includes age, parity, gestational age, bishop score, indication of induction, and maternal outcome. And data was analyzed by using EMI software. Results: Timely induction of labor can reduce maternal morbidity and ensure the delivery of a healthy baby. Among 200 consenting women 58.5% were multigravida and 41.5% were primigravida. Most common indication of induction among study participants is prolong rupture of membrane which is 35.5%. Among them 71.4% had vaginal delivery having poor bishop score. Most common indication for LSCS were fetal distress (34.8%). Conclusions: We concluded that elective induction of labor was associated with lower rates of LSCS and improved maternal and neonatal outcome.